What Advantages Arise from the Shift Towards Sustainable Energy Sources in Resource-Rich Economies? Empirical Insights from Azerbaijan - Gasimli, Vusal; Huseyn, Ramil; Huseynov, Rashad (International Journal of Energy Economics and Policy, 2024)
Azerbaijan, a nation with abundant petroleum resources, aspires to harness the untapped potential of the Caspian Sea’s renewable energy resources. The aim for the immediate future is to meet not only domestic energy requirements, but also to establish the nation as a green energy exporter. The nation expects to develop power installations utilizing renewable energy over the forthcoming decades to satisfy a portion of its domestic consumption and also cater to the European market. As part of this colossal project, Azerbaijan anticipates collaborating with international partners to install a 4-gigawatt (GW) power cable traversing the seabed of the Black Sea. The successful realization of these ambitious projects would bolster Azerbaijan’s economic sustainability during its post-petroleum phase, while simultaneously enabling a reduction in carbon emissions, offering regional and global benefits. This manuscript seeks to probe the multidimensional implications—political, economic, sociocultural and environmental—of this shift towards wind-derived green energy for Azerbaijan and other nations in the region.